2023
DOI: 10.3389/fpls.2023.1091588
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient genetic transformation system for broccoli and subcellular localization

Abstract: IntroductionAgrobacterium-mediated genetic transformation has been widely used for the identification of functional genes and regulatory and developmental mechanisms in plants. However, there are still some problems of low genetic transformation efficiency and high genotype dependence in cruciferous crops.MethodsIn this study, broccoli, a worldwide Brassica crop, was used to investigate the effects of genotype, explant type, concentration of hygromycin B used during seedling selection, overexpression vector ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The transformation efficiency is comparable to that of other ornamental flower plants, such as Chrysanthemum morifolium Ramat (the transformation efficiency is between 1% and 8%) [ 47 , 48 , 49 ], Broccoli oleracea var. italica (2.7–6.4%) [ 27 ], B. oleraceae var Botrytis (7–13.6%) [ 50 ], and L. pumilum DC Fisch (5.7–13.0%) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transformation efficiency is comparable to that of other ornamental flower plants, such as Chrysanthemum morifolium Ramat (the transformation efficiency is between 1% and 8%) [ 47 , 48 , 49 ], Broccoli oleracea var. italica (2.7–6.4%) [ 27 ], B. oleraceae var Botrytis (7–13.6%) [ 50 ], and L. pumilum DC Fisch (5.7–13.0%) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the Agrobacterium strain and concentration, genotype, explant type, and co-cultivation time significantly influence transformation efficiency [ 47 , 48 , 49 , 50 ]. There are different kinds of antibiotics to distinguish transgenic material from explants, such as kanamycin (Km) and hygromycin (Hyg), which were frequently applied to A. tumefaciens -mediated transformation methods for some woody plants [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the transformation efficiency of the Agrobacterium tumefaciens -mediated genetic transformation system for broccoli is generally approximately 2–26%, which is influenced by the explant type, receptor genotype, hormone concentration, culture time, and other factors [ 109 , 110 ]. In general, the broccoli genotype is the main factor affecting the efficiency of genetic transformation [ 44 , 109 ].…”
Section: Construction and Optimization Of The Genetic Transformation ...mentioning
confidence: 99%
“…It has been reported that the transformation efficiency of the Agrobacterium tumefaciens -mediated genetic transformation system for broccoli is generally approximately 2–26%, which is influenced by the explant type, receptor genotype, hormone concentration, culture time, and other factors [ 109 , 110 ]. In general, the broccoli genotype is the main factor affecting the efficiency of genetic transformation [ 44 , 109 ]. It has been established that when the concentration of hygromycin B is 5 mg/L for the generation of young sprouts, significant differences in the differentiation rate are usually detected among broccoli genotypes.…”
Section: Construction and Optimization Of The Genetic Transformation ...mentioning
confidence: 99%
See 1 more Smart Citation